The Illusion of Choice: The fabrication of social order through voluntary prison labor in the Dutch carceral system - Bouter,Madeleine (2026)
This thesis examines to what extent, and in what ways, voluntary prison labor in the Dutch carceral system is part of the fabrication of social order. The fabrication of social order is defined by Mark Neocleous as a massive policing operation by the state to manage the insecure, yet integral heart of the social order, poverty, by enforcing wage labor and domination by capital. Since 2021, prison labor is no longer mandatory in Dutch prisons, but voluntary. Prison labor must formally be organized to foster rehabilitation and resocialization. Based on ethnographic research consisting of semi-structured interviews with prison laborers, and fieldwork observations on the work floors of two medium-security prisons, this study analyzes how prison laborers experience voluntary prison labor, and to what extent this can be understood through Mark Neocleous’ theory of the fabrication of social order. The findings of the ethnographic research identify four main themes which shape the experience of participants: the illusion of choice in partaking in prison labor, the absence of self-identification of a laborer, labor differentiation and the notion of individual responsibility. Taken together, the research finds that voluntary prison labor functions as a part of the fabrication of social order, in two main ways. First, the change from mandatory to voluntary prison labor constitutes a liberal sublation of the coercive labor relations in the prison. Second, the structure of voluntary prison labor results in a social order in the prison akin to that of society at large, resulting in the acquiescence and acceptance of the social order. This study adds to existing literature on prison labor by shifting the debate from perceiving prison labor as purely punitive or rehabilitative, to perceiving prison labor as part of the fabrication of social order.
Keywords: Voluntary prison labor; Dutch prisons; the fabrication of social order; the myth of liberalism; poverty; wage class